Reconstruction of Imam Al Ghazali's Thinking abaut Pre-School Children Education in the Book Ihya Ulum al-Dien - Murom, Asep Saidul (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
nature that really contributes to the development of children. The choice of this title was inspired by Imam Al-Ghozali's thoughts which focused on children's education. And the phenomenon in society, including in family life, especially in educating children to believe in entrusting their children to servants, as a result of which the potential of children is not noticed by the parents/family itself as well as the lack of family attention and affection. Then educational institutions that provide preschool education that tend to be procedural and do not heed the potential of children and the education needed at the age of the child. For this reason, the author is awakened to reconstruct Imam Al-Ghozali's thoughts about children's education and relate it to the learning of preschool children at this time. With the following description: 1. How is the reconstruction of Imam Al-Ghozali's thoughts on pre-school education in the book Ihya Ulumuddin? 2. What is the relevance of Imam Al-Ghozali's thoughts on children's education with the current practice of preschool children's learning?The method used in this research is the method of content analysis (content analysis) and the method of study (Library research). Sources of data obtained from primary data, namely the book Ihya Ulum Al-Din by Imam Al-Ghozali. And secondary data, namely data obtained from other books, namely Ithaf sadatil Mutaqin, At-Tahliyah Wa At-Targib, Ta'lim Al-Muta'alim and books related to research conducted by the author.From the results of these studies resulted in a conclusion; 1. The reconstruction of Imam Al-Ghozali's thoughts on preschool education includes aspects of education, educational tools and family education, 2. Imam Al-Ghozali's thoughts on children's education remain relevant to preschool education at this time, but Imam Al-Ghozali's educational method is patterned Sufism and in practice preschool education today is more structural but the essence is the same